2021
DOI: 10.1007/s40487-021-00170-4
|View full text |Cite
|
Sign up to set email alerts
|

Does Breast Cancer Surgery Impact Functional Status and Independence in Older Patients? A Narrative Review

Abstract: Surgery is the recommended treatment modality for primary breast cancer. Breast cancer surgery is non-visceral; therefore, it is often assumed that the subsequent impact on functional status in older women is less significant compared to other cancer types such as colorectal cancer. Evidence for this however, is lacking. The definition of functional status varies amongst healthcare professionals and patients, making comparisons between studies difficult. From the literature, the two most common themes in relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The ability to estimate mortality following an intervention is extremely important in the setting of breast cancer at diagnosis, where a range of treatment options exist [ 30 ]. Although breast cancer surgery is deemed less morbid than surgery for other types of cancers, other studies have shown that functional status does decline after breast cancer surgery and severity of decline is associated with extent of surgery [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to estimate mortality following an intervention is extremely important in the setting of breast cancer at diagnosis, where a range of treatment options exist [ 30 ]. Although breast cancer surgery is deemed less morbid than surgery for other types of cancers, other studies have shown that functional status does decline after breast cancer surgery and severity of decline is associated with extent of surgery [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported a negative impact of mastectomy on the functional independence of the patient. More extensive surgery and co-morbidities may predict subsequent functional decline [12]. Following mastectomy, musculoskeletal complications such as pain, reduced joint mobility and reduced muscle strength cause functional decline.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of OBS are manifold, and include reducing the need for more extensive surgery with mastectomy and reconstruction, along with improvements in aesthetic and quality-of-life outcomes 10–13 . Studies 14 , 15 have shown that functional status can decline after breast cancer surgery, and this is compounded by the intensity of the surgery itself. Therefore, OBS may be better than mastectomy with reconstruction in preserving functional status in older women.…”
Section: Introductionmentioning
confidence: 99%